The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/polym10030328
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Capability, Physicochemical Properties, and Biocompatibility of nTiO2 Incorporated Polymeric Scaffolds

Abstract: Postoperative infection is a common risk which brings about failure in bone transplantation. In this study, nano titanium dioxide (nTiO2) was incorporated into Polyetheretherketone/polyglycolicacid (PEEK/PGA) blends to construct antibacterial scaffolds via selective laser sintering. Antibacterial capability was assessed using Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). The results demonstrated that the scaffolds with nTiO2 presented an effective antibacterial activity, which might be attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Among organic nanofillers, CNTs (carbon nanotubes) and graphene appear to be an effective reinforcement for the preparation of PVA nanocomposites [26,48], but they have a drawback related to the high production costs and low dispersion in the polymer matrix. The mineral nanofillers include different clays, metallic nanoparticles (Ag, Au) and metal oxide nanoparticles (TiO 2 , SiO 2 , Al 2 O 3 , ZrO 2 ), being developed depending on the final application of the prepared nanocomposite [2,17,20,21,23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among organic nanofillers, CNTs (carbon nanotubes) and graphene appear to be an effective reinforcement for the preparation of PVA nanocomposites [26,48], but they have a drawback related to the high production costs and low dispersion in the polymer matrix. The mineral nanofillers include different clays, metallic nanoparticles (Ag, Au) and metal oxide nanoparticles (TiO 2 , SiO 2 , Al 2 O 3 , ZrO 2 ), being developed depending on the final application of the prepared nanocomposite [2,17,20,21,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the corrosion resistance and thermo-mechanical stability, the advantages of TiO 2 in implant and tissue engineering applications are related to the formation of HA via the Ti-OH site and the ability to accelerate bone growth [2]. Another advantage is the antibacterial activity of TiO 2 in the form of nanoparticles, which demonstrated better inhibition of bacterial growth, with broad-spectrum antimicrobial action [2,17]. It has been demonstrated that TiO 2 nanoparticles have higher bioactivity than conventional (micron) particle sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Under UV irradiation, TiO 2 nanocrystals can effectively generate ROS, such as hydroxyl radicals (OH) and other reactive oxygen species, including superoxide anion (O 2 − ) and hydrogen peroxide (H 2 O 2 ). The ROS can interact with the cell wall through chemical binding, thus inactivating the phosphorus species and eventually causing bacterial death [46]. With the additional doping of Ag NPs, Ag NPs act as electron traps, and the electron transferring from TiO 2 to Ag can further inhibit the recombination of photon-generated electron/hole pairs, as confirmed by the red shift of light adsorption in UV-vis diffuse reflectance spectra (DRS) and its estimated decreased band gap (as shown in Figure 8), which promoted the formation of more ROS.…”
Section: Resultsmentioning
confidence: 99%
“…PEEK is non-toxic [156] but biologically inert [155] with a long biodegradation time [162]. To control degradation rates, PEEK has been blended with other polymers such as PGA (percentage weight loss after 28 days of 10.57% for 20% PGA, 12.88% for 40% PGA, 8.64% without nano-TiO 2 , and 9.72% with nano-TiO 2 [163,164]) and poly-L-lactide (PLLA) (up to 14% weight loss over 28 days for 50 wt% PLLA [165]) although further studies on its degradation products and their bio-absorbability are required. SLS was used to fabricate scaffolds in both cases, with incorporated nano-TiO 2 particles for an anti-bacterial function and β-TCP particles for bioactivity and biodegradability, respectively.…”
Section: Biocompatibility Biodegradability and Bioactivitymentioning
confidence: 99%